Tratamento penal do indígena sob uma perspectiva do multiculturalismo: análise dos casos de estupro de vulnerável e neonaticídio - Arlindo Corrêa de Almeida (2023)
This work’s central objective is to analyze the rape of vulnerable people and indigenous neonaticide, practiced within the cultural context in which they live, considering Brazil as a multicultural country. Such practices are misunderstood and generate concerns in a large part of national society, which provokes State intervention, through the application of Criminal Law in these cases and, sometimes, attributing criminal liability to indigenous people. From this situation, the reflection arises: should the indigenous people who carry out such practices, based on their cultures, be held criminally responsible by the Brazilian State? To answer this question, an exploratory qualitative research was carried out, aiming to follow solid paths capable of solving the problem, with an approach to criminal dogmatics, in particular, the Theory of Crime. Because the theme encompasses interdisciplinary issues, in addition to bibliographic sources in the area of Law, bibliographic sources in the area of Anthropology were also researched, with the aim of better understanding indigenous culture and its cosmology. Due to the relevance of the topic, international, constitutional and infra-constitutional issues were faced, related to fundamental rights, the rights of indigenous peoples and the application of Law. By facing theoretical and legal issues that deal with indigenous rights and cultural diversity, Combined with the criminal dogmatic systematization relevant to the topic, it was possible to identify solutions for the cases researched. It is concluded that, in the case of rape of a vulnerable person, the existence of material typicality is essential for the complete formation of one of the elements of the crime and its lack causes the atypicality of the conduct with the incidence of the principle of social adequacy, as a form of remove criminal liability from the agent; and in the case of neonaticide, due to the lack of awareness of the illegality, there will be a direct prohibition error that will also bring the same legal consequence as the previous case